2021
DOI: 10.3390/pharmacy9030128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quality Indicators on Beliefs about Medicines Reuse: An Experimental Study

Abstract: Background: A number of studies have examined beliefs about medicines reuse. Although the practice is prohibited in UK community pharmacy, it does take place elsewhere in the world where it relies on visual checks of returned medicines as an indicator of their quality. One proposal is to integrate sensor technology onto medication packaging as a marker of their quality instead. Our aim was to gauge people’s beliefs about medicines reuse, in an experiment, with or without sensor technology and with or without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Some respondents, especially from Tanzania, Uganda, Ghana, Indonesia, Malaysia and Saudi Arabia, give unused medications to family, acquaintances, friends or neighbors [ 24 , 26 , 28 , 37 , 56 , 57 ]. The reuse of unused pharmaceuticals is against the law in many countries, e.g., Poland or the UK, and taking such donated drugs may have negative effects on health, due to the conditions of their storage or the fact that they may be inappropriate [ 56 , 58 ]).…”
Section: Methods Of Disposal Of Unused/expired Pharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some respondents, especially from Tanzania, Uganda, Ghana, Indonesia, Malaysia and Saudi Arabia, give unused medications to family, acquaintances, friends or neighbors [ 24 , 26 , 28 , 37 , 56 , 57 ]. The reuse of unused pharmaceuticals is against the law in many countries, e.g., Poland or the UK, and taking such donated drugs may have negative effects on health, due to the conditions of their storage or the fact that they may be inappropriate [ 56 , 58 ]).…”
Section: Methods Of Disposal Of Unused/expired Pharmaceuticalsmentioning
confidence: 99%
“…Research conducted in the Netherlands and Great Britain showed that over 50% of respondents were willing to use medications returned unused to the pharmacy by another patient as long as the quality of these medicines was verified [ 130 , 131 ]. In addition, an experiment by Lam et al (2021) in Great Britain showed that the integration of sensors that measure and track the interaction of the storage conditions (e.g., temperature, light, humidity) on drug packaging, and the guarantee that the quality of drugs will be visually assessed by the pharmacist, meant that the respondents would be more willing to participate in a system for the reuse of medications [ 58 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…A potential solution being explored is the use of temperature and humidity sensor labels, which are cheap, convenient and already in common use in the food and automotive industries, and even by the pharmaceutical industry in other parts of the supply chain 24 . Their addition to drug packaging would not only help to maintain safety, but previous qualitative research has shown such technology improves willingness to accept reused medicines among patients 25 …”
Section: Ensuring Safety and Efficacymentioning
confidence: 99%
“…Stability is dependent on the actual drug ingredients, presence of preservatives, temperature fluctuations, light, humidity, and other conditions. Innovative work in the United Kingdom's “Reuse of Medicines Through Informatics, Networks and Digital Sensors” project combines sensor technology with the internet of things to indicate the “reusability” (based on quality indicators and safety checks) of unopened medicines (Lam et al, 2021). Successful schemes have been launched in The Netherlands, the United States, and Greece (GIVMED, 2022; OECD, 2022).…”
Section: Addressing Pharmaceutical Wastagementioning
confidence: 99%